2019
DOI: 10.2478/jomb-2018-0020
|View full text |Cite
|
Sign up to set email alerts
|

Age and Assay Related Changes of Laboratory Thyroid Function Tests in the Reference Female Population

Abstract: Summary Background: Laboratory thyroid function tests play a central role in the diagnosis of thyroid disorders. The aim of our cross-sectional study was to determine reference values for thyroid tests in a rigorously selected group of Montenegrin females, investigate the impact of possible age-related changes and the influence of the interassay bias between three frequently used immunoassays. Methods: Female subjects were randomly selected, aged between 20 and 69 and 946 of them met the selection criteria. TS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 39 publications
0
3
0
Order By: Relevance
“…In this survey, 13,344 individuals with no family or personal history of thyroid disease, goiter, thyroid laboratory abnormality, and use of interfering medication but with positive TgAb and TPOAb were examined. Recent European studies showed a TSH RI of 0.44 to 4.13 mIU/L in women aged between 19 and 70 years (electrochemiluminescence method -Roche Diagnostics ® ) (24) and of 0.65 to 5.39 mIU/L in women aged between 20 and 69 years (chemiluminescent immunoassay -Architect i2000 platform, Abbott Laboratories ® ) (25).…”
Section: Discussionmentioning
confidence: 99%
“…In this survey, 13,344 individuals with no family or personal history of thyroid disease, goiter, thyroid laboratory abnormality, and use of interfering medication but with positive TgAb and TPOAb were examined. Recent European studies showed a TSH RI of 0.44 to 4.13 mIU/L in women aged between 19 and 70 years (electrochemiluminescence method -Roche Diagnostics ® ) (24) and of 0.65 to 5.39 mIU/L in women aged between 20 and 69 years (chemiluminescent immunoassay -Architect i2000 platform, Abbott Laboratories ® ) (25).…”
Section: Discussionmentioning
confidence: 99%
“…In order to assess the thyroid functioning, it is recommended to measure the level of thyroid-stimulating hormone (TSH) secreted by the pituitary gland and the free triiodothyronine (FT 3 ) and free thyroxine (FT 4 ) in the blood [7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…The two most common causes of hyperthyroidism are Graves' disease (GD) and toxic nodular goitre (1). The prevalence of hyperthyroidism is 0.8% in Europe and 1.3% in the USA (2,3).…”
Section: Introductionmentioning
confidence: 99%